1999
DOI: 10.1034/j.1399-3011.1999.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin uptake stimulating peptide found in plasma of normal individuals and in some autistic urines

Abstract: We have isolated a tripeptide from normal plasma and autistic urines which stimulates the uptake of serotonin (5-HT) into platelets. This peptide was purified by high-performance liquid chromatography (HPLC) and characterized by sequenation and mass-spectrometry. Synthetic peptide showed co-chromatography with the biological sample in the HPLC systems used. Close to 60% of the autistic children diagnosed using the Diagnostic Statistical Manual III-R had an increased HPLC peak eluting like this peptide in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The possible involvement of carboxypeptidases in the pathology of autism is raised by several reports of abnormal patterns of urinary peptides in some individuals with autism. [19][20][21] Although these findings have failed to be replicated by other studies and remain controversial, 22 it is possible that altered pancreatic peptidase function could lead to an unusual accumulation of peptides. Furthermore, the presence of CPA gene transcripts has been identified at low levels in extrapancreatic tissues, namely in brain, where they could potentially participate in signalling events such as biosynthesis or inactivation of peptide messengers.…”
Section: Introductionmentioning
confidence: 48%
“…The possible involvement of carboxypeptidases in the pathology of autism is raised by several reports of abnormal patterns of urinary peptides in some individuals with autism. [19][20][21] Although these findings have failed to be replicated by other studies and remain controversial, 22 it is possible that altered pancreatic peptidase function could lead to an unusual accumulation of peptides. Furthermore, the presence of CPA gene transcripts has been identified at low levels in extrapancreatic tissues, namely in brain, where they could potentially participate in signalling events such as biosynthesis or inactivation of peptide messengers.…”
Section: Introductionmentioning
confidence: 48%
“…2 This finding was considered inconsistent with reports of low serum levels of serotonin, until the discovery that platelet serotonin levels were also high for autistic children. 19 Pedersen et al 20 have since identified opioid peptide fragments within the urine of autistic children that stimulate serotonin uptake by platelets. It seems possible that, with a high uptake of serotonin by platelets, an increase in serotonin synthesis might result, depleting levels of tryptophan and causing a reduction in urinary levels.…”
Section: Discussionmentioning
confidence: 99%
“…A chemical candidate for this reactive inhibition and habituation is serotonin. We found a peptide from autistic urines (pyroGlu-Trp-GlyNH2) that increased the uptake of serotonin into platelets (Pedersen et al, 1999) and into synapses in the CNS (Persico et al, 1998). Increased platelet serotonin is a frequently reported finding in autism (Rogeness et al, 1992).…”
Section: Poor Habituationmentioning
confidence: 96%